Custo da preparação do relato financeiro: o caso Português - Paiva, I.; Carlos, T. (XXIII Workshop on Accounting and Management Control, 2018)
Regarding accounting harmonization between countries, the accouting standards pick an important role in financial reporting and for their multiple financial information stake holders. Both small and micro-entities are an extremely important segment either nationally and at European level. There is exclusive standards for this particular kind of entities in Portugal that intend to suit these smaller businesses own financial reporting needs. In this sense, the simplified standards existing in Portugal aim to reduce the burden that comes from over demanding financial reporting requirements regarding these smaller entities nature. So, the purpose is to avoid higher disproportionately costs incur relatively to larger companies. This study goal is to evaluate the use of simplified standards for this kind of companies. The analysis is built through the costs perceptions gathered form accountants on the subject of the simplification coming from this specific standards. The usefulness of this analysis is relevant and the results obtained from research depict a critical look on the applicable accounting standards structure in Portugal.